Підготовка вчителів-жінок півдня України у другій половині ХІХ - на початку ХХ століття. (Zaporizhzhia Historical Review, 2021)
The article highlights the problem of female teachers’ preparation in South Ukraine province in second part of XIX- early XX century. The author analyzes system of educational institutions for teachers’ preparation, exposes the issue of teachers’ financial and social situation, the level of their professional competence.